2016
DOI: 10.1177/1099636216658895
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear free and forced vibration analysis of embedded functionally graded sandwich micro beam with moving mass

Abstract: In this study, nonlinear free and forced vibration analysis of an embedded functionally graded sandwich micro-beam with a moving mass is investigated. The velocity of moving mass is assumed constant. The structure is resting on nonlinear Pasternak foundation. The governing equation of motion is obtained using Hamilton's principle based on the Euler–Bernouli model with considering nonlinear terms in strain–displacement relation. Strain gradient elasticity theory is used to model the small scale effects. The mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…By substituting variations of the strain and electric field components and integration over the thickness of sandwich nanoplate, the variation of strain energy can be expressed as (24) in which N ij ; M ij are resultants of force and moments that are defined as…”
Section: Governing Equations Of Motionmentioning
confidence: 99%
See 2 more Smart Citations
“…By substituting variations of the strain and electric field components and integration over the thickness of sandwich nanoplate, the variation of strain energy can be expressed as (24) in which N ij ; M ij are resultants of force and moments that are defined as…”
Section: Governing Equations Of Motionmentioning
confidence: 99%
“…A parametric study was presented to investigate effect of the small scale parameter, thicknesses layers, external electric and magnetic loads and mode numbers on critical buckling load of magneto-electro-elastic sandwich nanoplate. Nonlinear free and forced vibration analysis of sandwich micro beam carrying a moving mass resting on nonlinear Pasternak foundation was studied by Arefi et al 24 Euler-Bernouli model with considering nonlinear terms according to the Von-Karman strain-displacement relations and strain gradient elasticity theory was used to obtain governing equations of motion. Nonlinear ordinary differential equations were discretized by Galerkin's technique.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on Hamilton’s principle, the vibrational form of equations of motion can be written as [36]: in which, U , K , and Σ represent total strain energy, total kinetic energy, and external work of system, respectively.…”
Section: Equations Of Motion Based On Hamilton’s Principlementioning
confidence: 99%
“…Nonlinear analysis of nanotube-reinforced composite beams resting on elastic foundations in thermal environments was studied by Shen and Xiang [22] that derived the motion equations based on higher-order shear deformation beam theory and concluded that thermal postbuckling path of unsymmetric FG-CNTRC beams is no longer the bifurcation type. Nonlinear free and forced vibration analysis of embedded functionally graded sandwich micro-beam with moving mass was performed by Arefi et al [23]. They illustrated the effect of some important parameters such as power gradient index, aspect ratio, position, and velocity of moving mass on the nonlinear natural frequency.…”
Section: Introductionmentioning
confidence: 99%